Comparative Study between Laser Hemorrhoidoplasty and Open Hemorrhoidectomy in a Tertiary Center, Pokhara - Timilsina, Bishow Deep; Subedi, Babita (Journal of Nursing and Health Sciences Nepal, 2025)
Introduction: Hemorrhoidal disease is a common anorectal disorder affecting a significant portion of the adult population. While conventional hemorrhoidectomy remains the standard surgical approach for treating hemorrhoidal disease, several minimally invasive procedures have emerged in recent years as alternative options for managing hemorrhoids. Nonetheless, studies report inconsistent outcomes of different methods in terms of symptom resolution. Thus, our study was caried out to evaluate the effectiveness of laser hemorrhoidoplasty (LHP) versus Milligan–Morgan hemorrhoidectomy (MMH). Methods: This prospective observational study was carried out at a Manipal Teaching Hospital from October 2024 to July 2025, following ethical approval from Institutional Review board (IRB No. MCOMS/ IRC/598/GA). A total of 60 patients with symptomatic grade II and III hemorrhoids were enrolled. Participants were randomly assigned into two groups: 30 patients underwent LHP and 30 underwent MMH. The study focused on evaluating duration of surgery, intraoperative bleeding, pain levels and early postoperative factors like bleeding, urinary retention, constipation, abscess edema and, return to normal activities. Results: Patients in the LHP group experienced significantly lower levels of postoperative pain, reduced operative time, less intraoperative blood loss, shorter hospital stays, less abscess and constipation (p<0.001). There was no statistically significant difference between the two groups in terms of postoperative bleeding, urinary retention, edema. Conclusion: Laser Hemorrhoidoplasty presents a favorable alternative to the traditional Milligan- Morgan hemorrhoidectomy for treating II- and III-degree hemorrhoids. It offers multiple advantages, including decreased postoperative pain, shorter procedure time, quicker recovery, and reduced intraoperative blood loss.